SYNTHESIS CHARACTERISTICS OF NALTA AND CALTA MOLECULAR SIEVES VIA CHEMICAL ACTIVATION AND HYDROTHERMAL METHODS - Abdulhayev A.B; Ergashev O.K; Toshmatova B.A (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This scientific article presents the synthesis technology of molecular sieve structures of the LTA-type zeolites modified with sodium and calcium cations – NaLTA and CaLTA – via chemical activation and hydrothermal methods. The study explores the mechanochemical activation of raw materials using impact-vibration milling, their preparation for crystallization, and the mechanisms of phase structure formation. The resulting microporous frameworks were evaluated using physicochemical characterization techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer–Emmett–Teller surface analysis (BET), and infrared spectroscopy (IR), with a particular focus on determining their adsorption properties.